Mediatisasi Dakwah melalui Kesenian Habsyi di Regei Lestasi, Kalimantan Tengah - Herles Anwar; Abdul Gani; Siti Zainab (Ath Thariq Jurnal Dakwah dan Komunikasi, 2020)
This article was aimed at explaining the da'wah mediation through the Habsyi art in Regei Lestari village, Central Kalimantan. The method applied in this study was qualitative method. Data were collected through observations, interviews, and documentary studies. Through such data collection, this study found that the Habsyi art plays an important role in socio-religious life of Regei Lestari’s society. This important role can be seen from the existence of the Habsyi art in every social-religious activity of Regei Lestari’s society. Awareness of this important role is also the basis for da'wah mediation through the Habsyi art in Regei Lestari. The implication of this mediation was that there was a change of both the quality and quantity of society’s participation in da'wah activity. Therefore, based on these findings, it can be concluded that art is not only on purpose as a medium to provide entertainment for humans, but also in certain society, it can be as a fairly effective da'wah medium as in Regei Lestari society. Keywords : The mediation of da'wah, Habsyi, Regei Lestari